The Effect of Livelihood Assets on Living Strategies: An Empirical Study of Farmer Household Characteristics - Illu, Abraham; Muhaimin, Abdul Wahib; Setiawan, Budi (Garuda Prestasi Nusantara Consulting, 2021)
This study aims to analyze the effect of livelihood assets and demographics on the implementation of farmers' livelihood strategies in Pandansari Village, Ngantang District, Malang Regency after the eruption of Mount Kelud. This research is a type of quantitative research that uses Structural Equation Modeling (SEM) analysis with the Warp PLS approach. Primary data were obtained through in-depth interviews using questionnaires and field observations, while secondary data obtained through literature studies from various related sources. It was determined the location deliberately considering that Pandansari Village was the area in Ngantang District that was the worst affected by the eruption of Mount Kelud. Seventy-five farmers with simple random sampling technique were selected as respondents in this study. The results showed that livelihood assets had a positive but insignificant effect on demographics. Then livelihood assets have a positive and significant influence on livelihood strategies. Meanwhile, demographics have a negative and significant impact on livelihood strategies. Keywords : Sustainable Livelihoods, Livelihood Assets, Livelihood Strategies, Eruption, Structural Equation Modeling (SEM), WarpPLS.